THE IMPACT OF SCIENCE FOUNDATION PROGRAMMES ON THE SUCCESS RATE OF FIRST-YEAR STUDENTS IN A BLENDED TEACHING AND LEARNING ENVIRONMENT. - Snyman, L. W.; Kasirye, M. (South African Journal of Higher Education, 2021)
This article highlights some successes as achieved with an extended Science Foundation Provision Programme for first-year engineering students at the University of South Africa's Science and Engineering School in Johannesburg. The learners were mainly from disadvantaged environments. Strategies ranged from upgradation of study material, intensive monitoring of online study activities; the appointment of online tutors to assist students; as well as the introduction of face-to-face tutor classes held regularly throughout the course. Owing to these strategies, the online activity of students active in modules in Civil and Chemical Engineering grew on average from about 50% to about 80%; that of students active in Electrical and Mining Engineering improved from 40% to 60%; and that of students active in Mechanical and Industrial Engineering went up from 20% to about 60%. Correspondingly, students' success rate increased up to 40% in Chemical Engineering, up to 45% in Electrical Engineering and up to 40% in Mechanical and Industrial Engineering. Even in challenging cognitive subjects such as Chemical Processing, and Digital and Analogue Electronics, students coped well. It is believed that several lessons can be learned by other environments from this exercise.